Multipoint Wrist Pulse Acquisition and Analysis by Combining HRV with Morphological Timing Features for Quantitative Identification of Ayurvedic Doshas - Devendra Patel; Mitul Patel (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2026)
Nadi Pariksha, the traditional Ayurvedic method of wrist pulse examination, posits that three adjacent radial artery locations corresponding to Vata, Pitta, and Kapha (V-P-K) reflect distinct physiological states. While recent sensor-based systems have attempted to digitize wrist pulse acquisition, many have emphasized hardware design or classification performance without rigorously validating physiological differences between pulse sites within the same individual. This study presents a quantitative evaluation of the multi-point principle of Nadi Pariksha using synchronized multi-site photoplethysmography (PPG) combined with integrated cardiovascular signal analysis. Pulse waveforms were simultaneously acquired from 39 participants, including 32 healthy individuals and 7 clinically characterized subjects, at the three classical radial artery locations. Morphological timing features and time-domain heart rate variability (HRV) metrics were extracted to characterize vascular dynamics and autonomic regulation. Within-subject statistical analysis demonstrated significant spatial differentiation across the pulse sites. Crest time decreased from 0.204 s at the Kapha site to 0.175 s at the Vata site (14.2% reduction), while systolic width decreased from 0.140 s to 0.109 s (22.1% reduction) (p ≤ 0.004). Non-parametric analysis confirmed significant differences in crest time (H = 9.15, p = 0.010), pulse width (H = 8.43, p = 0.015), systolic amplitude, systolic area, and HRV variability (SDNN: H = 6.33, p = 0.041), with moderate-to-large effect sizes (η² = 0.12–0.20). Clinically characterized cases exhibited deviations from this baseline pattern, including a 62% reduction in crest time gradient and a 72% increase in stiffness index in diabetes, and a 55% reduction in gradient with a 25% decrease in HRV during acute infection. Given the limited clinical sample (n = 7), these findings are interpreted as preliminary. Overall, the results provide quantitative within-subject evidence supporting the physiological distinctiveness of the V-P-K pulse locations and contribute toward the development of standardized, sensor-based Nadi Pariksha